2003
DOI: 10.1172/jci18141
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–accelerated atherosclerosis and aneurysm formation is attenuated in osteopontin-deficient mice

Abstract: mice expressed less CD68, C-C-chemokine receptor 2, and VCAM-1. In response to intraperitoneal thioglycollate, recruitment of leukocytes in OPN -/-mice was impaired, and OPN -/-leukocytes exhibited decreased basal and MCP-1-directed migration. Furthermore, macrophage viability in atherosclerotic lesions from Ang II-infused ApoE -/-OPN -/-mice was decreased. Finally, Ang II-induced abdominal aortic aneurysm formation in ApoE -/-OPN -/-mice was reduced and associated with decreased MMP-2 and MMP-9 activity. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 59 publications
5
158
0
4
Order By: Relevance
“…These findings promoted us that the similar mechanism may exist in the development of aortic aneurysm. Bruemmer et al discovered that the development of AAA in the rats which had been knocked out gene of OPN was suppressed [15] . The findings of Nakashima et al revealed that treatment with NF-κB inhibitors could lead to the similar results [16] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings promoted us that the similar mechanism may exist in the development of aortic aneurysm. Bruemmer et al discovered that the development of AAA in the rats which had been knocked out gene of OPN was suppressed [15] . The findings of Nakashima et al revealed that treatment with NF-κB inhibitors could lead to the similar results [16] .…”
Section: Discussionmentioning
confidence: 99%
“…193 Key mechanisms include VSMC senescence, 194 oxidative stress, 12,195 increased local production of proinflammatory cytokines, and increased MMPs activities that degrade the extracellular matrix. 196 Chronic AngII infusion into apolipoprotein E knockout mice promotes aortic aneurysm formation. 197,198 In animal models of aortic aneurysm, genetic and pharmacological inhibition of ROS production 199,200 and MMPs 201,202 suppressed the development of aneurysm.…”
Section: Rho-kinase In Vascular Diseasesmentioning
confidence: 99%
“…Recently, it was reported that deficiency of osteopontin decreased Ang II-induced AAA formation in apolipoprotein E -/-mice [25]. Osteopontin was originally identified as a molecule that mediates osteoclast adhesion to mineralized matrix.…”
Section: Modes Of Inhibiting Angiotensin Ii-induced Abdominal Aortic mentioning
confidence: 99%